2023
DOI: 10.1021/acsnano.2c12373
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and Exciton Binding Energy Effects on Hot Carrier Cooling in Lead Halide Perovskite Nanomaterials

Abstract: The relaxation of the above-gap ("hot") carriers in lead halide perovskites (LHPs) is important for applications in photovoltaics and offers insights into carrier−carrier and carrier−phonon interactions. However, the role of quantum confinement in the hot carrier dynamics of nanosystems is still disputed. Here, we devise a single approach, ultrafast pump− push−probe spectroscopy, to study carrier cooling in six different size-controlled LHP nanomaterials. In cuboidal nanocrystals, we observe only a weak size e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 115 publications
1
13
1
Order By: Relevance
“…The calculated values of r exc and |ϕ n (0)| 2 are listed in Table , showing that the excitonic lifetime in KNbO 3– x Q x compounds increases with increasing the concentration of Q (=S, Se), and it also increases from S to Se at a given x . Since the electronic structure of a material, which is determined by its bonding, can affect the recombination rate of electron–hole pairs and, thus, the excitonic lifetime, the increasing exciton lifetime from S to Se, is attributed to the strengthening of covalent bonding in the resulting compound. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated values of r exc and |ϕ n (0)| 2 are listed in Table , showing that the excitonic lifetime in KNbO 3– x Q x compounds increases with increasing the concentration of Q (=S, Se), and it also increases from S to Se at a given x . Since the electronic structure of a material, which is determined by its bonding, can affect the recombination rate of electron–hole pairs and, thus, the excitonic lifetime, the increasing exciton lifetime from S to Se, is attributed to the strengthening of covalent bonding in the resulting compound. , …”
Section: Resultsmentioning
confidence: 99%
“…Since the electronic structure of a material, which is determined by its bonding, can affect the recombination rate of electron−hole pairs and, thus, the excitonic lifetime, the increasing exciton lifetime from S to Se, is attributed to the strengthening of covalent bonding in the resulting compound. 29,30 The KNbO 3−x Q x (x = 1, 2) are polar compounds with a fairly large dynamical charge as explained in Table 1, and it is therefore of great importance to identify if lattice polarizability contributes to E B and the dressing up of the QP with the virtual phonon in these compounds. The excitation of the characteristic longitudinal optical phonon of the polar materials induces a large macroscopic crystal field that can strongly couple to the excitons.…”
Section: Optical Excitations the Optical Absorption Spectra Of Knbomentioning
confidence: 99%
“…Solution-processed two-dimensional hybrid perovskite (2DHP) films have attracted more and more attention as a promising candidate for a broad spectrum of optoelectronic applications as well as unique excitonic and polaronic dynamics. With organic cations (A) isolating a single inorganic layer made by Pb–X octahedral units (X is a halide ion), 2DHPs (A 2 PbX 4 ) exhibit an intrinsic multiquantum well (MQW) structure, in which excitons are spatially confined in inorganic layers upon optical excitation, i.e., quantum confinement effect. Moreover, largely distinguished dielectric properties of organic and inorganic layers lead to strong dielectric screening on excitons and carriers. As the result, 2DHPs usually exhibit an order of magnitude higher exciton binding energy ( E b ) than that of 3DHPs without the MQW structure, which comprises a basis of optoelectronic properties of 2DHPs. …”
Section: Introductionmentioning
confidence: 99%
“…PNCs have garnered much interest because of their facile synthesis, , high photoluminescence quantum yields (PLQYs), and defect tolerance. Several HC studies have thus been devoted to elucidating whether such an intrinsic phonon bottleneck can be utilized in PNCs. Early reports on the synthetic methods of PNCs mainly involved sizes in the moderate to weak confinement regime, ,,, and hence, earlier HC studies largely focused on weakly confined PNCs. Later, PNCs with sizes smaller than their Bohr diameter were successfully synthesized via traditional hot-injection methods that allowed access to the strongly confined regime. , Nevertheless, there are conflicting reports on the existence of an intrinsic phonon bottleneck in confined PNCs. ,, Some studies have suggested the presence of such an intrinsic phonon bottleneck in PNCs through examination of size-dependent HCC rates. ,, On the contrary, several other studies have suggested efficient breaking of intrinsic bottlenecks through nonadiabatic coupling, , enhanced electron–phonon coupling, and efficient Auger processes. , However, the comparability between studies is encumbered by the usage of different PNC synthesis methods in these reports, which may strongly influence the interpretations . This problem could be exacerbated by the influence of HC traps that also play a role in the HC relaxation of PNCs. , Most recently, facile room-temperature slow-growth methods have been developed for more controllable synthesis of PNCs with various compositions over a wider range of sizes exhibiting strong to weak confinement. , This provides new opportunities to re-examine the effect of QC on HCC behavior in PNCs and reassess the existing controversy.…”
Section: Introductionmentioning
confidence: 99%